ORGANIZATIONAL AND ECONOMIC POWERS IN THE PROCESS OF ORGANIZATION, MANAGEMENT, REGULATION AND CONTROL OF ECONOMIC ACTIVITY - Кухарчук, Анастасія Миколаївна (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2020)
Introduction. The issue of legal research of organizational and economic powers is constantly in the focus of researchers in the field of both economic and administrative law. There are different views on the emergence of organizational and economic powers. Some scholars believe that such powers arise exclusively in the process of managing economic activity, others - both in the process of management and in the process of regulating economic activity. In particular, the issues of organization and control of economic activity are added to such discussions. Accordingly, as a result of which processes the organizational and economic powers arise today are not so clearly defined at the legislative or doctrinal levels. Topicality. Given this uncertainty regarding the processes during which organizational and economic powers arise, many questions and problems arise during their implementation. In particular, this problem is manifested in the separation of organizational and economic and power powers, especially when the subject is simultaneously endowed with the functions of power and organizational and economic nature in the process of managing economic activity. Accordingly, the analysis of the concepts of organization, management, regulation and control of economic activity in the context of the theory of economic and administrative law and the theoretical and legal perspective needs its justification and systematic scientific disclosure. Summary of the main results of the research. The definition of these concepts at the legislative and doctrinal levels has been worked out. The concept of organization of economic activity is studied, which is proposed to be considered broadly (as an independent direction of activity aimed at rational combination in time and space of all elements of economic system of appropriate level: national (sectoral), local (regional), at the level of economic entities); and narrow meanings (as a management function that is implemented in the process of unification (distribution) of subjects, objects, means and is designed to create a new or reorganize or liquidate the existing system). It is established that economic management is an independent type of activity that is implemented in relation to social relations that arise, change and cease in connection with the implementation or realization of the intention to conduct economic activity on the basis of property relations on the basis of property, control relations. -subordination and delegated powers in order to effectively implement it. It is proposed to consider state regulation of economic activity at the macro and micro levels. It is investigated that control is one of the management function. Conclusions. It is substantiated that organizational and economic powers arise in the process of business management and or regulation of economic activity (at the micro level). It is proposed to include in the Commercial Code of Ukraine the following definition of organizational and economic relations: “organizational and economic relations in this Code mean the relations between business entities and subjects of organizational and economic powers in the process of economic management and / or economic regulation. activities (at the micro level)".